Copper Imbalance in Alzheimer’s Disease and Its Link with the Amyloid Hypothesis: Towards a Combined Clinical, Chemical, and Genetic Etiology - Rosanna Squitti; Peter Faller; Christelle Hureau; Alberto Granzotto; Anthony R. White; Kasper P. Kepp (2021)
The cause of Alzheimer's disease (AD) is incompletely defined. To date, no mono-causal treatment has so far reached its primary clinical endpoints, probably due to the complexity and diverse neuropathology contributing to the neurodegenerative process. In the present paper, we describe the plausible etiological role of copper (Cu) imbalance in the disease. Cu imbalance is strongly associated with neurodegeneration in dementia, but a complete biochemical etiology consistent with the clinical, chemical, and genetic data is required to support a causative association, rather than just correlation with disease. We hypothesize that a Cu imbalance in the aging human brain evolves as a gradual shift from bound metal ion pools, associated with both loss of energy production and antioxidant function, to pools of loosely bound metal ions, involved in gain-of-function oxidative stress, a shift that may be aggravated by chemical aging. We explain how this may cause mitochondrial deficits, energy depletion of high-energy demanding neurons, and aggravated protein misfolding/oligomerization to produce different clinical consequences shaped by the severity of risk factors, additional comorbidities, and combinations with other types of pathology. Cu imbalance should be viewed and integrated with concomitant genetic risk factors, aging, metabolic abnormalities, energetic deficits, neuroinflammation, and the relation to tau, prion proteins, α-synuclein, TAR DNA binding protein-43 (TDP-43) as well as systemic comorbidity. Specifically, the Amyloid Hypothesis is strongly intertwined with Cu imbalance because amyloid-β protein precursor (AβPP)/Aβ are probable Cu/Zn binding proteins with a potential role as natural Cu/Zn buffering proteins (loss of function), and via the plausible pathogenic role of Cu-Aβ.